Recentralization of Mining Licensing Authority and Its Impact on Local Autonomy in Indonesia - Tinambunan, Hezron Sabar Rotua; Istislam; Hadiyantina, Shinta; Kusumaningrum, Adi; Tajudin, Amalina Ahmad (Jurnal Suara Hukum, 2025)
The principle of decentralization is a constitutional mandate that grants authority to regional governments to administer governance and manage natural resources within their respective jurisdictions. This principle emerged as a corrective measure to the centralized governance model of the New Order regime, which had resulted in significant disparities in welfare between the central government and the regions. Law Number 4 of 2009 on Mineral and Coal Mining initially reinforced this decentralization by delegating the authority to issue Mining Business Permits (IUP) to local governments, thereby contributing to the enhancement of local community welfare in resource-rich regions. However, the enactment of Law Number 3 of 2020, which amended Law Number 4 of 2009, reversed this decentralization by reassigning such authority to the central government. This legislative shift represents a constitutional anomaly, contradicting the decentralization spirit embedded within the 1945 Constitution of the Republic of Indonesia. This study employs normative legal research methods using statutory and conceptual approaches to examine the division of authority between the central and regional governments in managing the mineral and coal mining sector. The findings reveal that the recentralization of IUP authority not only undermines regional autonomy but also adversely affects the development of resource-producing regions and hampers the realization of social justice as envisioned in the framework of a welfare state.